2023
DOI: 10.1002/cssc.202301311
|View full text |Cite
|
Sign up to set email alerts
|

Furandicarboxylate Polyesters: A Comprehensive ADMET Study of a Novel Class of Furan‐Based α,ω‐Diene Monomers

Beatriz Chícharo,
Sami Fadlallah,
Florent Allais
et al.

Abstract: The present research article delves into the preparation of a new class of bio‐based polyesters from α,ω‐diene furandicarboxylate monomers. In particular, it exploits the use of acyclic diene metathesis polymerisation (ADMET) on 2,5‐furandicarboxylic acid (FDCA)‐derived compounds. First, a library of furan‐based α,ω‐diene monomers was prepared via acid‐ or base‐catalyzed transesterification of 2,5‐furandicarboxylic acid dimethyl ester (FDME) with commercially available alcohols incorporating terminal olefins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…To obtain high-molecular-weight polymers, the byproduct ethylene was removed under a continuous vacuum. It has been demonstrated that the carbon chain length of monomers had an impact on ADMET polymerization, which reflected as the longer alkyl length between olefins and functional groups improved polymerization efficiency. ,, HF and UF with multiple methylene groups (4 and 9) between olefin and ester groups were synthesized for ADMET polymerization (entries 1 and 2, Table ), and the corresponding homopolymers PHF and PUF were obtained with the number-average molecular weights ( M n ) of 14.6 and 15.1 kDa (Figure S9), respectively. The presence of heteroatoms such as oxygen atoms in the ether group and carbonyl group can cause the poisoning of metal in the catalyst to some extent and thus alter the activity of the catalyst itself .…”
Section: Resultsmentioning
confidence: 99%
“…To obtain high-molecular-weight polymers, the byproduct ethylene was removed under a continuous vacuum. It has been demonstrated that the carbon chain length of monomers had an impact on ADMET polymerization, which reflected as the longer alkyl length between olefins and functional groups improved polymerization efficiency. ,, HF and UF with multiple methylene groups (4 and 9) between olefin and ester groups were synthesized for ADMET polymerization (entries 1 and 2, Table ), and the corresponding homopolymers PHF and PUF were obtained with the number-average molecular weights ( M n ) of 14.6 and 15.1 kDa (Figure S9), respectively. The presence of heteroatoms such as oxygen atoms in the ether group and carbonyl group can cause the poisoning of metal in the catalyst to some extent and thus alter the activity of the catalyst itself .…”
Section: Resultsmentioning
confidence: 99%
“…Shifting our attention to environmentally friendly polymerization methods, ADMET (acyclic diene metathesis) polymerization emerges as an intriguing option due to its catalytic nature and the generally moderate temperatures required for polymerization. Moreover, its characteristic of not necessitating solvents further enhances its appeal. Simultaneously, the development of biobased phenolic monomers derived from lignin has already been a focal point of research during the past decade. , Numerous studies have investigated the synthesis of new olefinic monomers from lignin-derived molecules, such as ferulic acid or vanillin (Table S1, Supporting Information, SI).…”
Section: Introductionmentioning
confidence: 99%